2017
DOI: 10.22159/ijpps.2017v9i6.17671
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pain Score in Osteoarthritis Patients Treated With a Combination of Diacerein and Meloxicam and Meloxicam Alone

Abstract: Objective: Osteoarthritis (OA) is a progressive chronic disease with the loss of articular cartilage. In managing OA, inadequate pain relief (IPR) often occurs, particularly with a single non steroidal anti-inflammatory drugs (NSAIDs) therapy. In this research, pain outcome of OA patients treated with a combination of diacerein and meloxicam vs meloxicam alone was evaluated.Methods: This research was conducted at rumah sakit umum daerah (RSUD) Dr. Mohammad Soewandhie Surabaya by using randomized controlled tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…The mean age of this study population was 61.65±7.55 years. A study conducted by Ohtori et al showed that the mean age of patients was 70.0±8 years [8,9]. As per the study results, female patients (58.34%) were more suffered by OA than male (41.66%) patients.…”
Section: Discussionsupporting
confidence: 60%
“…The mean age of this study population was 61.65±7.55 years. A study conducted by Ohtori et al showed that the mean age of patients was 70.0±8 years [8,9]. As per the study results, female patients (58.34%) were more suffered by OA than male (41.66%) patients.…”
Section: Discussionsupporting
confidence: 60%
“…Osteoarthritis is a progressive disease characterized by the degeneration of cartilage and joint tissue changes that cause pain, stiffness, and disability [1]. The disease is common in the elderly causing disability in old ages [2,3]. The incidence of osteoarthritis increases with age and is estimated about 80% of the population aged 65 years proven radiologically.…”
Section: Introductionmentioning
confidence: 99%
“…Meloxicam which is classified as NSAID has an analgesic function, anti-inflammatory, and antipyretic. However, long-term use has an impact on the side effects, particularly on the gastrointestinal system, including dyspepsia, gastric mucosal irritation, and bleeding [2]. The utilization of medicinal plants for the treatment of hereditary has been used and provided good results.…”
Section: Introductionmentioning
confidence: 99%
“…In managing OA, inadequate pain relief often occurs, particularly with single non-steroidal anti-inflammatory drugs (NSAIDs) therapy [1]. OA is the joint inflammation and degenerative process that have a direct influence on limiting the quality of life and well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms will be prevalent while engaging with weight-bearing activities such as walking, climbing stairs, and standing from a chair [2]. Sit to stand is the common activity of daily living performed by everyone, limitations in this may add burden that impacts people's quality of life and reliance on health-care needs [1].…”
Section: Introductionmentioning
confidence: 99%